2005
DOI: 10.1097/01.tp.0000158023.21233.de
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Immunosuppressants on Induction of Regulatory Cells After Intratracheal Delivery of Alloantigen

Abstract: Generation of regulatory cells by ITD of alloantigen was facilitated by mycophenolate mofetil and high doses of rapamycin but abrogated by cyclosporine A, azathioprine, and high doses of FK506. Low doses of rapamycin and of FK506 did not interfere with generation of regulatory cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…In our model, UDCA induced indefinite survival of fully allogeneic grafts when given with a short course of low-dose FK506, an agent that induced prolonged, but not indefinite, allograft survival when administered alone. We previously showed that a low dose of FK506 does not interfere with the induction of regulatory cells (19). In contrast, administration of a short course of low-dose CyA in our model resulted in rejection of cardiac allografts, even when UDCA, which induced indefinite allograft survival when given alone, was given concurrently.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…In our model, UDCA induced indefinite survival of fully allogeneic grafts when given with a short course of low-dose FK506, an agent that induced prolonged, but not indefinite, allograft survival when administered alone. We previously showed that a low dose of FK506 does not interfere with the induction of regulatory cells (19). In contrast, administration of a short course of low-dose CyA in our model resulted in rejection of cardiac allografts, even when UDCA, which induced indefinite allograft survival when given alone, was given concurrently.…”
Section: Discussionmentioning
confidence: 66%
“…We previously found that CyA abrogated the induction of regulatory cells in our murine cardiac transplantation model, whereas a low dose (0.1 mg/kg) of FK506 did not interfere with this induction (19). In this study, we assessed whether CyA or FK506 was compatible with prolongation of allograft survival after treatment with UDCA that resulted in generation of regulatory cells.…”
Section: Prolonged Survival Of Allografts In Mice Treated With Ursodementioning
confidence: 91%
See 1 more Smart Citation
“…Thus, the lack of effect of Rapa on the number of Tregs (the present study), together with the normal function of Tregs in patients treated with the Rapa derivative everolimus (25), suggests that mTOR have an advantage in promoting immunologic tolerance over CNI. Besides, mycophenolate mofetil (MMF), which also acts in the IL-2 signaling pathway, facilitates the generation of regulatory cells, as demonstrated in different mouse models of transplantation tolerance (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CNIs are potent blockers of IL-2 production but IL-2 is critically important for the survival of Tregs [94]. In our murine model, mycophenolate mofetil and high doses of rapamycin facilitated induction of Tregs and low doses of tacrolimus or rapamycin did not interfere with it; however, cyclosporine A, azathiopurine, and high doses of tacrolimus abrogated Treg induction [95]. Future research on the role of purified EPA in strategies for inducing immune tolerance in clinical transplantation must include studies in large animals.…”
Section: Future Directions: Purified Epa In Clinical Organ Transplantmentioning
confidence: 69%